THU0394 Long-Term Therapy with Canakinumab in Two Patients with Refractory Chronic Autoinflammatory Arthritis. (10th June 2014) - Skendros, P.; Papagoras, C.; Oikonomou, A.; Apostolidou, E.; Konstantinidis, T.; Kambas, K.; Mitroulis, I.; Ritis, K.
Abstract : Background: Canakinumab, a human anti-IL-1β monoclonal antibody, has been licensed for the treatment of cryopyrin-associated periodic syndrome (CAPS), while few reports have shown benefit in patients with refractory familial Mediterranean fever (FMF). However, clinical experience regarding long-term administration of canakinumab in rare autoinflammatory syndromes, such as FMF, has not been described to date 1, 2 . Objectives: To report the long-term efficacy and safety of canakinumab in two adults with chronic arthritis associated with mutations in the MEFV gene, refractory to conventional treatments. Methods: Two patients with refractory chronic autoinflammatory arthritis were treated with canakinumab for a total of 42 and 24 months, respectively. The first patient (P1) was a 25 year-old female, homozygous for the MEFV M694V mutation, suffering from typical FMF with additional severe destructive arthritis of both hips and the left knee. Her arthritis had been resistant to colchicine, prednisolone, methotrexate and etanercept, while anakinra elicited severe injection site reactions 2 . The second patient (P2) was a 26 year-old female, with clinical characteristics shared between CAPS and FMF, homozygous for the R202Q mutation in MEFV . She suffered from chronic inflammatory polyarthritis resistant to colchicine and glucocorticoids and, although she had initially responded to anakinra, the drug was discontinued due to hypersensitivity reactions. Background colchicine was maintained in both cases. Clinical assessments, VAS pain/morning stiffness of the affected joints, VAS global assessment and acute phase reactants (CRP, ESR) were recorded every 4 weeks. MRI of the affected joints were performed at baseline and after treatment initiation. Results: In P1 canakinumab was administered at a dose of 150 mg at weeks 0, 8, 14, 20 and every 4 weeks thereafter. The dose interval was shortened aiming to keep the patient symptom-free for the whole inter-dose interval. In P2 canakinumab was administered at a dose of 150 mg/8 weeks. Both patients soon experienced a significant improvement of the articular symptoms and remained in clinical remission during the rest of treatment. Neither patient experienced any systemic inflammatory attack during the treatment period. Further, canakinumab produced a normalization of acute phase reactants in P2 and moderate reductions in P1. In P1 follow-up MRI demonstrated focal areas of bone marrow edema, thickened synovium and chronic subchondral degenerative changes, which, however, remained stable over the 3-year period. In P2 complete radiological remission was evident on MRI. In both patients, canakinumab treatment allowed colchicine reduction to a minimal dosage. Overall, canakinumab was well tolerated and no adverse events were noted. Conclusions: Our report suggests that canakinumab is effective and safe in patients with difficult to treat chronic autoinflammatory arthritis. These observations encourage the conduct of prospective clinical trials of canakinumab in FMF. References: Soriano A, et al. Clin Rev Allergy Immunol. 2013;45:117. Mitroulis I, et al. Ann Rheum Dis. 2011;70:1347. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2249